The Influence of Art Nouveau on Furniture Design: A Holistic Understanding of Interior Space - Salbacak, Salih (Süleyman Demirel Üniversitesi, 2025)
This study examines the impact of the technological, social, and cultural transformations brought about by the Industrial Revolution in early 20th-century Europe on the understanding of art and design. The aim of the research is to evaluate the Art Nouveau movement, which emerged as a reaction against the monotony caused by mass production, within the context of architecture, interior design, and furniture design. A historical and descriptive method was employed, analyzing the interactions between the socio-cultural structure of the period, artistic movements, and modes of production. The findings indicate that Art Nouveau developed differently across various regions of Europe, shaped by local cultural dynamics, and that it dissolved the boundaries between art and craft through the use of organic forms inspired by nature. Furthermore, the study examines the iconic furniture pieces created by prominent artists of the period, included in the Art Nouveau furniture collection at the Musée d’Orsay in Paris. The analysis reveals that furniture during this era was regarded not only as a functional object but also as a medium of aesthetic and artistic expression. In conclusion, Art Nouveau is identified as a pivotal movement that laid the foundations for modern design thinking.

Bu çalışma, 20. yüzyılın başlarında Avrupa’da Sanayi Devrimi’nin yarattığı teknolojik, toplumsal ve kültürel değişimlerin sanat ve tasarım anlayışına etkisini incelemektedir. Araştırmanın amacı, seri üretimin neden olduğu tekdüzeliğe tepki olarak gelişen Art Nouveau sanat akımını mimari, iç mimari ve mobilya tasarımı bağlamında değerlendirmektir. Çalışmada tarihsel ve betimsel bir yöntem izlenmiş; dönemin sosyo-kültürel yapısı, sanat hareketleri ve üretim biçimleri arasındaki ilişkiler irdelenmiştir. Bulgular, Art Nouveau’nun Avrupa’nın farklı ülkelerinde yerel kültürel dinamiklerle biçimlendiğini ve doğadan ilham alan organik formlarla sanat ile zanaat arasındaki sınırları ortadan kaldırdığını göstermektedir. Ayrıca Paris Musée d’Orsay’daki Art Nouveau mobilya koleksiyonunda yer alan dönemin önemli sanatçılarının ikonik mobilyaları incelenmiştir. Bu dönemde mobilyanın yalnızca işlevsel değil, aynı zamanda estetik ve sanatsal bir ifade aracı olarak görüldüğü ortaya konmuştur. Sonuç olarak, Art Nouveau modern tasarım düşüncesinin temelini oluşturmuştur.
Art Nouveau’nun Mobilya Tasarımına Etkisi: Bütüncül İç Mekân Anlayışı
Keywords: Art Nouveau; Holistic İnterior Architecture Design; Furniture; Bütüncül İç Mimari Tasarım; Mobilya